PERBAIKAN KUALITAS PEMBELAJARAN DALAM PBM SEJARAH SOSIAL - Musadad, Akhmad Arif (Jurnal Inovasi Pendidikan, 2007)
The objectives of research are: (1) to encourage the students history of study program to be more active in attending the lecture, (2) to improve the lecturer's capability in arranging the lesson plan, (3) to improve the lecturer's capability in implementing the learning procedure, and (4) to improve the lecturer's capability in managing the class. This research was a classroom action research. This research consists of actions aiming at improving the quality of system and practices within the system. This research is reflective in nature, aiming at improving the rational establishment of the action taken. This research was conducted in two cycles. In order to improve the learning quality, the researcher takes some measures: discussion of history learning effectiveness, discussion of class management, RPP preparation practice, peer teaching, and the use of group investigation learning model. From such measures, it can be seen that the learning quality improves from a cycle to another. This is reflected from: the increasing capability of the lecturer in preparing RPP, the increasing capability of the lecturer in implementing the learning procedure, and the increasing capability of the lecturer in managing the class. These improvements also lead to the improvement of students' learning activity. In addition, the capability of managing the class also results in the improvement of learning circumstance.